Mycophenolate Mofetil in the Treatment of Psoriasis. Issue 1 (March 2014) - Leung, Christy; Anvekar, Rina
Psoriasis is a chronic immune-mediated disorder which, though not life-threatening, has a great impact on the quality of life. There are multiple therapeutic options available for the treatment of psoriasis based on the severity and percentage of body surface area involved which include topicals, systemic agents, and phototherapy. It is not uncommon for patients to become resistant to therapies and treatment failures can be frustrating for the physician as well as the patient. Mycophenolate mofetil, an antimetabolite and immunosuppressant, has been found to be effective and safe for treating moderate-to-severe psoriasis in several studies. It is a good alternative for patients who fail traditional systemic treatments or who have a contraindication for their use.